PRIMENA FRAKTALNE I TEKSTURALNE ANALIZE U MEDICINSKOJ FIZIOLOGIJI, PATOFIZIOLOGIJI I PATOLOGIJI - Pantic, Igor; Jovana; Radojević - Škodrić, Sanja (Medical Research, 2022)
Fractal and textural analyses represent a rapidly developing class of computational and mathematical methods with potential wide applications in medicine and biology. In recent years, they have been successfully used for evaluation of subtle alterations in cell and tissue morphology associated with various physiological and pathological processes. It was shown that cells in early stages of apoptosis exhibit changes in chromatin fractal and textural features. Cellular senescence is also sometimes associated with changes in textural pattens in some cell populations. So far, artificial intelligence approaches based on co-occurrence matrix textural data were successfully implemented for prediction of cell damage in in vitro conditions, with artificial neural networks achieving the best performance. In the future, several methodological issues and challenges related to the use of fractal and textural methods will have to be resolved before their introduction to contemporary clinical practice. This concise review focuses on the recent research on the application of fractal and textural methods in experimental physiology and related fields.